The Effects of Non-Invasive Brain Stimulation on Quantitative EEG in Patients With Parkinson's Disease: A Systematic Scoping Review - Costa, Thaísa Dias de Carvalho; Godeiro Júnior, Clécio; Silva, Rodrigo Alencar e; dos Santos, Silmara Freitas; Machado, Daniel Gomes da Silva; Andrade, Suellen Marinho (Frontiers in Neurology, 2022)
Parkinson’s Disease (PD) is a progressive neurodegenerative disorder characterized by motor and non-motor symptoms, aside from alterations in the electroencephalogram (EEG) already registered. Non-invasive brain stimulation (NIBS) techniques have been suggested as an alternative rehabilitative therapy, but the neurophysiological changes associated with these techniques are still unclear. We aimed to identify the nature and extent of research evidence on the effects of NIBS techniques in the cortical activity measured by EEG in patients with PD. A systematic scoping review was configured by gathering evidence on the following bases: PubMed (MEDLINE), PsycINFO, ScienceDirect, Web of Science, and CINAHL. We included clinical trials with patients with PD treated with NIBS and evaluated by EEG pre-intervention and post-intervention. We use the criteria of Downs and Black to evaluate the quality of the studies. Repetitive transcranial magnetic stimulation, transcranial electrical stimulation, electrical vestibular stimulation, and binaural beats are non-invasive stimulation techniques used to treat cognitive and motor impairment in PD. This systematic scoping review found that the current evidence is suggestive that NIBS could change quantitative EEG in patients with PD. However, considering that the studies’ quality varied from poor to excellent, the low number of studies, variability in NIBS intervention, and quantitative EEG measures, we are not yet able to use the EEG outcomes to predict the cognitive and motor treatment response after brain stimulation. Based on our findings we recommend additional research efforts to validate EEG as a biomarker in noninvasive brain stimulation trials in PD.